1999
DOI: 10.1148/radiographics.19.6.g99no011447
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Papillary Mucinous Tumor of the Pancreas: A Pictorial Essay

Abstract: Intraductal papillary mucinous tumor (IPMT) of the pancreas was identified and classified only recently. IPMT has a primarily intraductal, papillomatous growth pattern, which is associated with excessive mucin secretion and results in progressive ductal dilatation or cyst formation. The tumor occurs in four forms: segmental or diffuse involvement of the main pancreatic duct and macrocystic or microcystic involvement of a branch duct. In the past, many IPMTs may have been misdiagnosed as chronic pancreatitis be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(82 citation statements)
references
References 25 publications
1
77
0
1
Order By: Relevance
“…In addition, the presence of thickened irregular walls/septa on MDCT also correlated well with malignancy. Procacci et al [17] reported that in malignant lesions, the wall and septa appear irregular and thick, indicating intramural nodules, whereas both the wall and septa are regular and thin in benign lesions. Carbognin et al [18] reported that the presence of a thick wall by CT and MR imaging is strongly suggestive of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of thickened irregular walls/septa on MDCT also correlated well with malignancy. Procacci et al [17] reported that in malignant lesions, the wall and septa appear irregular and thick, indicating intramural nodules, whereas both the wall and septa are regular and thin in benign lesions. Carbognin et al [18] reported that the presence of a thick wall by CT and MR imaging is strongly suggestive of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 75% of IPMTs originate from the main pancreatic duct within the head of the pancreas (3). Imaging of IPMTs is important not only to identify the tumor but also to determine the appropriate treatment strategy in relation to the site and size of the lesion (2). Although the presence of a dominant mass of considerable size (as in the present case) is a rare occurrence, it should not preclude the diagnosis of IPMT.…”
Section: Discussionmentioning
confidence: 73%
“…IPMTs occur with equal frequency in male and female subjects, and the peak time of occurrence is the 6th decade of life, regardless of sex (2). Approximately 75% of IPMTs originate from the main pancreatic duct within the head of the pancreas (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the identification of vascularized inclusions (Figure 4), and for the differential diagnosis between MCA and a pseudocyst [17,46] . IPMNs are cystic tumors of the pancreas recently reported with increasing frequency [6,38,41,47,48] . They are macroscopically characterized by having an intraductal origin and growth [49] , with the production of dense mucin that fills the main pancreatic duct (the ductectatic mucin-hypersecreting variant) or with endoluminal papillary proliferation (the papillary-villous variant).…”
Section: Mucinous Cystic Tumorsmentioning
confidence: 99%